A reassessment of combinations previously proposed or published for Kalanchoe subg. Alatae (Crassulaceae subfam. Kalanchooideae), and its valid publication at the rank of subgenus - Smith, Gideon F. (Phytotaxa, 2023)
Article 35.2 of the Shenzhen Code requires that, for a combination to be validly published, authors of plant names must: “[…] definitely associate the final epithet with the name of the genus or species, or with its abbreviation […]”. Correct application of this Article indicates that neither “Kalanchoe sect. Alatae” nor “Kalanchoe subg. Alatae”, was validly published by, respectively, Raymond-Hamet in 1933 and Smith et al. in 2021. However, Kalanchoe sect. Alatae was validly published by Smith in 2021. The new status, at the rank of subgenus, Kalanchoe subg. Alatae, is validly published here.